Theoretical and strategic background to the work of NGOs in defending human rights - MAALEM, Youcef; BOULOUSAKH, Imene (Journal of Human Sciences, 2020)
International and national human rights non-governmental organizations have become an inalienable reality, an indisputable fact. Thus they have become an authority against the power, and the voice of the oppressed, who find no support in the face of tyranny and the domination of dictatorial powers. Despite his voluntary and non-profit work and the eventual harassment, persecution and even physical liquidation of its members, NGOs have taken human rights as a message and a moral value that they defend. despite their neutrality. They strive to have material and human potential, and follow the latest technologies and the most effective strategies to fulfill its function and ensure the success of its noble mission.This is the general context of this article which set itself as problematic what are the backlogs: theoretical? NGO work strategy? and the mechanisms created for this purpose.